Plan de marketing estratégico para la empresa EMPROVIT de la ciudad de Pujilí. - Zumárraga Ortiz, Jaime Eduardo (2022)
This research is oriented to a strategic marketing plan for EMPROVIT, a company with more than 19 years, which has managed to grow and prevail over time thanks to the tenacity of its owners; however, the situational diagnosis reveals that, at present, due to the dizzying changes in the environment, competition and extreme events, its sales levels and market share have decreased. In this sense, it has been necessary to establish an objective to guide the phases of the research, which is related to the need to design a strategic Marketing Plan for the company; these actions are methodologically supported by the quantitative approach with the use of tools and models such as PESTEL and SWOT, which served as input for the design of FO-DO and FA - DA strategies, as well as for the analysis of strategic positioning and the approach of basic strategies in accordance with the McKinsey matrix. As part of the results, a market segmentation process was carried out using an unsupervised artificial intelligence model (cluster) to define the three most representative customer profiles or "Buyer Persona" of the company, which allowed estimating a market potential of approximately 91 million dollars per year. Finally, the consolidated strategic marketing plan is presented, whose strategies are aligned with the marketing objectives and the marketing mix, which are operationalized through activities, responsible, costs and estimated annual revenues.